QUALITY CONTROL TESTING OF CONVENTIONAL CLOPIDOGREL BISULFATE TABLETS MARKETED IN IRAQ - ABDUL-HASAN, MAZIN THAMIR; Al-SHAIBANI, ABULFADHEL JABER NEAMAH; WANNAS, ALI N.; HASAN AL-GBURI, KARRAR MOHAMMED (International Journal of Applied Pharmaceutics, 2022)
Objective: This study was employed to evaluate the quality of marketed oral tablets containing clopidogrel bisulfate. Tablets produced by various companies and commercialized in the Iraq market were used in the study. Methods: Batches of clopidogrel bisulfate conventional tablets (containing 75 mg of drug) were exposed to the quality control tests. These tests involved friability, weight variation, hardness, drug content, disintegration time, and in vitro release study; these tests were conducted depending on USP pharmacopeia. Results: The data indicate that all batches of clopidogrel bisulfate complied with the limitations of USP pharmacopeia for variation of weight, results of the hardness of tablets were 7.2-9.6 Kg/cm2. Friability value (% loss) was less than one, which was within the required limits. The time of disintegration was less than 25 min in both artificial gastric fluid (AGF) and artificial intestinal fluid (AIF). Drug content was observed between 97.1 % and 99.8 %, indicating compliance with the limits of pharmacopeia (85-115 %). An in vitro release study of batches was greater than 80 % within 25 min. Conclusion: All batches of clopidogrel bisulfate were manufactured within the criteria of tablet manufacturing. The quality control tests of tablets showed acceptable pharmaceutical properties (effectiveness and safety) that lie within the limits of USP pharmacopeia.